The Effect Of Tourist Behavior On Sea Turtle Conservation Activities At The Serang Beach Marine Tourism Attraction - Bagaskara Harilinawan; Garsione Agni Andrea (Jurnal Toursci, 2026)
Background. The growth of the ecotourism sector in coastal areas faces challenges in the form of potential anthropogenic disturbances to the sensitive sea turtle ecosystem. Referring to Law No. 32 of 2024 on the Conservation of Biological Resources and Their Ecosystems Aims. This study aims to analyze the impact of tourist behavior on the success and effectiveness of sea turtle conservation activities in the Segoro Lestari Sea Turtle Conservation Area, a marine tourism attraction at Serang Beach, Blitar Regency. Methods. This quantitative associative-causal study examines the relationship between tourist behavior (attitudes, compliance, and participation) and conservation activities (tourist reception, education, and hatchling release). Data collection was conducted using a census/saturation sampling technique involving 55 tourists who directly participated in conservation activities. Validity and reliability tests of the instruments yielded valid and consistent indicators (Cronbach’s Alpha = 0.868). Result. The results of the simple linear regression analysis showed a regression equation of Y = 5.812 + 0.626X, with a calculated t-value of 6.451 > the critical t-value (2.006) and a significance level < 0.001. These results demonstrate that tourist behavior has a positive and significant effect on the effectiveness of sea turtle conservation activities. Conclusion. The coefficient of determination (R²) of 0.440 indicates that the tourist behavior variable accounts for 44.0% of the variation in the success of conservation activities.